MAKNA “AL-IQTIṢÂD ” DAN KORELASINYA DENGAN EKONOMI KONTEMPORER (TELA’AH AYAT-AYAT EKONOMI) - Luayyin, Reza Hilmy; Mohammad Arifin; Muhammad Nabat Ardli (LPPM STAI Muhammadiyah Probolinggo, 2024)
Many communities still misconception the concept of Islamic economics. In fact, a significant portion of the Muslim population itself is somewhat unfamiliar with the terms associated with Islamic economics. The terms